Investigating the Impact of Curriculum Literacy and Media Literacy on Job Self-Efficacy in Secondary School Teachers - Heidarizadeh, Nasrin (Iranian Journal of Educational Sociology, 2022)
Purpose: Self-efficacy as a part of self refers to belief and confidence to one's abilities to achieve goals and tasks. Therefore, the aim of this study was investigating the impact of curriculum literacy and media literacy on job self-efficacy in secondary school teachers. Methodology: The method of research was descriptive from type of correlation. The statistical population in this study were included all secondary school teachers in West Islamabad city in the academic years 2021-2022 with number of 260 people, which based on the Krejcie and Morgan table number of 165 people were selected by simple random sampling method. The research tools were included job self-efficacy, curriculum literacy and media literacy questionnaires, which were completed by the secondary school teachers and their reliability was estimated to be higher than 0.70. To answer the research hypotheses were used the confirmatory factor analysis tests and structural equation modeling in SPSS and LISREL software. Findings: The findings showed that the job self-efficacy variable has four components of individual self-efficacy beliefs, collective self-efficacy beliefs, expectation of individual consequences and expectation of collective consequences, curriculum literacy variable has three components of curriculum planning system, curriculum basics and curriculum planning elements, and media literacy variable has five components of understanding the content of media messages, awareness of the hidden goals of media messages, critical look at media messages, conscious selection and analysis of media messages, which factor load of all was calculated above 0.50 and Cronbach's reliability of all was calculated above 0.70. Also, both variables of curriculum literacy and media literacy had a direct and significant effect on the job self-efficacy of secondary school teachers (P